FINANCIAL BOOKKEEPING TRAINING FOR BUMDES AND MSME MANAGERS IN KANDANGAN VILLAGE, SENDURO SUBDISTRICT, LUMAJANG REGENCY: A PRE- AND POST-SURVEY TO IMPROVE UNDERSTANDING OF BUSINESS AND BUMDES FINANCIAL MANAGEMENT - Maharani, Rosa Melia; Rohman, Muhammad Syaikh; Harijanto, Catherine; Arifin, Sulton; Siti Syuhada Qanitah; Firda Ayu Fadhila; Widya Andika; Adela Ogya Gavrila (Jurnal Layanan Masyarakat (Journal of Public Services), 2025)
Kandangan Village, Senduro District, Lumajang, East Java is one of the villages with many agricultural and livestock potentials. Through the existence of Village-Owned Enterprises (BUMDes), this potential can provide benefits for the welfare of the village community. However, the limited financial bookkeeping capabilities of both BUMDes administrators and people who have businesses mean that the potential of Kandangan Village has not provided more benefits in increasing the local economy and income of BUMDes Kandangan Village. Through BUMDes Panca Karya Mandiri, Kandangan Village, Lumajang, East Java, in collaboration with the Faculty of Economics and Business, Airlangga University, held a training session to enhance the knowledge and skills of BUMDes and the village community in financial bookkeeping to support the improvement of the local economy. The implementation of this training was carried out for three days which took place at the Kandangan Village Hall. The use of pre-post training surveys in this training was used to measure the effectiveness of training activities on training participants. The results of the Wilcoxon Signed-Rank Test showed that there was an increase in understanding related to financial bookkeeping for training participants after the training was carried out.